Posterior Mediastinal Epithelioid Angiosarcoma Arising in Schwannoma: A Case Report and Review of the Literature - Xiang, Yingming; Yan, Liping; Lin, Xia; Zhang, Xiangyan; Zhang, Fangbiao; Wu, Zhijun (Frontiers in Surgery, 2021)
Epithelioid angiosarcoma arising in a schwannoma is an extremely rare mesenchymal tumor that accounts for only 1% to 2% of all sarcomas. It occurs in all parts of the body, most often in the skin and soft tissues, and rarely in the mediastinum. The present study describes the case of an asymptomatic, 58-year-old male who presented with an epithelioid angiosarcoma in the posterior mediastinum during a physical examination. Enhanced computed tomography of chest revealed a 3.5×3.1-cm mass in the posterior mediastinum. Due to the possibility that the tumor was malignant, thoracoscopic mediastinal mass resection was performed under general anesthesia. Pathological examination revealed the presence of angiosarcoma and schwannoma components. Immunohistochemical staining for cluster of differentiation (CD) 31, CD34, early growth response (EGR), vimentin, Sry related HMG box (SOX)-10 and S-100 were strongly positive. The patient recovered and was discharged on postoperative day 5. Two months post surgery, the patient was followed up and no evidence of tumor recurrence was observed.